2018
DOI: 10.1007/s10067-018-4316-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality in patients with fibromyalgia

Abstract: Introduction: Previous studies suggest personality, the multifaceted characteristics underlying a person’s affect, cognition, and behavior, may influence fibromyalgia. We examined associations among personality, fibromyalgia impact, and health-related outcomes in patients with fibromyalgia. We further tested whether anxiety and depression mediated the effect of personality on fibromyalgia impact. Methods: We performed a secondary analysis using baseline data from a randomized trial on fibromyalgia. Personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…Neuroticism positively correlated with stress, anxiety and depression. These results were also found by Vujičić and Ranđelović (2017) and Mostafaei et al (2019), and similar results were reported by other studies (Brailovskaia & Margraf, 2016;Ervasti et al, 2019;Gramstad et al, 2013;Milić et al, 2019;Mousavi & Essazadegan, 2016;Pereira-Morales et al, 2019;Seto et al, 2019;Sørengaard et al, 2019). In contrast, (A) negatively correlated with stress, anxiety and depression.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Neuroticism positively correlated with stress, anxiety and depression. These results were also found by Vujičić and Ranđelović (2017) and Mostafaei et al (2019), and similar results were reported by other studies (Brailovskaia & Margraf, 2016;Ervasti et al, 2019;Gramstad et al, 2013;Milić et al, 2019;Mousavi & Essazadegan, 2016;Pereira-Morales et al, 2019;Seto et al, 2019;Sørengaard et al, 2019). In contrast, (A) negatively correlated with stress, anxiety and depression.…”
Section: Resultssupporting
confidence: 90%
“…However, in the study by Vujičić and Ranđelović (2017) extraversion negatively influenced anxiety, and conscientiousness negatively predicts anxiety and depression. Morevover, the correlation between consciousness and depression was found previously by different studies (Seto et al, 2019;Vujičić & Ranđelović, 2017). Furthermore, extraversion was positively correlated with all three (stress, anxiety and depression) in the study by Brailovskaia and Margraf (2016) and Gramstad et al (2013) also found that extraversion protected against symptoms of depression.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Patients with FMS suffer not only from pain but also from a range of symptoms including cognitive dysfunction, fatigue, sleep disturbance, and somatic and psychological distress [25]. Because there is currently no cure for it, management of FMS usually focuses on symptom relief [6]. In this context, a number of patients with FMS have increasingly taken interest in complementary and alternative medicine and have used one or more complementary and alternative therapies [7].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with those of previous studies. 11,27 Seto, et al 27 found that higher neuroticism was associated with anxiety, depression, stress, and worse mental quality of life in fibromyalgia patients. We demonstrated that lower openness to experience was associated with poor cognitive function.…”
Section: Discussionmentioning
confidence: 99%